Lymphomas complicating primary Sjögren’s syndrome: from autoimmunity to lymphoma - Nocturne, Gaetane (Rheumatology (Oxford), 2019)
Lymphoma development is the most serious complication of SS and the main factor impacting on mortality rate in patients with this condition. Lymphomas in SS are most commonly extranodal non-Hodgkin B-cell lymphomas of the mucosa-associated lymphoid tissue and frequently arise in salivary glands that are the target of a chronic inflammatory autoimmune process. Extensive work on lymphomagenesis in SS has established that the progression towards B-cell lymphoma is a multistep process related to local chronic antigenic stimulation of B cells. These neoplastic B cells in SS frequently derived from autoreactive clones, most commonly RF-producing B cells, which undergo uncontrolled proliferation and malignant escape. In this review, we highlight the most important recent findings that have enhanced our understanding of lymphoma development in SS, with particular reference to the close link between autoimmunity and lymphomagenesis. We also discuss how the identification of key factors involved in B-cell malignancies may impact on our ability to identify at early stages patients at increased risk of lymphoma with potential significant repercussions for the clinical management of SS patients. Finally, we identified the most promising areas of current and further research with the potential to provide novel basic and translational discoveries in the field. The questions of finding new biomarkers, developing a validated score for predicting lymphoma occurrence and assessing if a better control of disease activity will decrease the risk of lymphoma in primary SS will be the enthralling questions of the next few years.